PRINCIPLES OF CONSTRUCTION OF EFFECTIVE INFORMATION SYSTEMS : J.J. Atamuradov - Atamuradov, Jamshid (Центр Научных Публикаций (buxdu.uz), 2021)
This article discusses the principles of building effective information systems and their classification.